How do people choose their commuting mode? An evolutionary approach to transport choices - Simone Borghesi; Chiara Calastri; Giorgio Fagiolo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2014)
The issue of transportation is of primary importance in our societies. A large share of green-house gases is generated by the transport sector, and road casualties are one am ong the most common causes of death. In the present work, we study commuter choice between alternative transport modes using an evolutionary-game model, wherein commuters can choose between using their private car or taking the bus. We examine the possible dynamics that can emerge in a homogeneous urban population, where agents are boundedly rational and imitate the others. We obtain a different number of equilibria depending on the values of the parameters of the model. We carry out comparative-static exercises and examine possible policy measures that can be implemented in order to modify the agents' payoff, an d consequently the equilibria of the system, leading the society towards more sustainable transportation patterns.
Keywords: C73; R4; D6; 330; Commuter choices; Transportation; Evolutionary dynamics; Environmental policy